Kuntowijoyo's Thoughts on Islamic Economics: Implementing the Use of Virtual Accounts in the Tuition Fee Payment System - Kholidatul Mila; Andira Alif Anggraini; Helmi Syaifuddin (al-Afkar, Journal For Islamic Studies, 2026)
The changes in social economy and the influence of globalization in Indonesia have resulted in social, economic, and political life patterns developing more widely. With this, Kuntowijoyo includes Islamic knowledge in the Indonesian economic system so that it becomes an Islamic economic system based on ethics, morals, and character in accordance with Islamic values. This study aims to describe the relevance of Kuntowijoyo's thoughts to one of the Islamic economic systems, namely the use of virtual accounts. This type of research is qualitative research with a data collection method, namely library research. The results of the study indicate that transactions using virtual accounts are permitted in Islamic law if they are in accordance with the terms of financing services related to payments through virtual accounts do not exceed reasonable limits, and the bank does not overdo it in taking advantage.